Presbyterians in North Carolina : Race, Politics, and Religious Identity in Historical Perspective. - Conser, Walter H. (University of Tennessee Press, 2011)
This volume is the first comprehensive overview of North Carolina Presbyterians to appear in more than a hundred years. Drawing on congregational and administrative histories, personal memoirs, and recent scholarship - while paying close attention to the relevant social, political, and religious contexts of the state and region - Walter Conser and Robert Cain go beyond older approaches to denominational history by focusing on the identity and meaning of the Presbyterian experience in the Old North State from the seventeenth through the twentieth centuries. Conser and Cain ex.